Geographical education I: fields, interactions and relationships - Puttick, Steven (Progress in human geography, 2022)
Complex global challenges, rapid shifts in the mediation and distribution of information, rising inequalities and a toxic milieu of low-quality public reasoning make geography education more important than ever. This first progress report explores the nexus of geography education research, geography education practice and scholarship and the geographies of education. Conceptualising the fields through expansive understandings positions this report in an optimistic space, highlighting significant opportunities for geography and its contribution to public reasoning through deepening collaborations and attending to tensions in education’s ‘shadow and shine’: tensions between its complicity in maintaining unjust hierarchies against its potential for emancipatory transformation.